Analysis of Disposed Unused Medications at a Village Community Pharmacy - Valerie Vella; Lorna-Marie West (MDPI AG, 2019)
Background: The aim of this study was to determine the type, quantity, and cost of medications being disposed of by clients in a specifically-set pharmaceutical disposal bin at a village community pharmacy. Methods: Medicines placed in a medication disposal bin by clients were examined during a nine-month period from April to December 2018. The data recorded included the active ingredient, trade name, dose, dosage form, disposed quantity, and the actual expiry date on the pack. The medications were classified according to ATC (Anatomical Therapeutic Chemical Classification System) code, and the cost of the amount wasted was calculated using the pharmacy’s price list. Descriptive statistics were used to analyze the data. Results: A total of 411 medications were collected, amounting to a total cost of approximately €2600. The largest group of medications belonged to the alimentary group, and this also represented the group with the highest monetary value. The number of months that medicinal products were retained by patients beyond the expiry date ranged from 1 to 232. Conclusion: This small study provides a glimpse of what clients dispose of in a medication bin when this is readily available in their community pharmacy, a simple measure which, if adopted on a national level, could aid in ensuring the appropriate disposal of wasted medication.